Knee-ankle kinematics and coupling responses to SportsMetrics training programs in females athletes with dynamic knee valgus: A sport-specific approach - Fakhraei Rad, Niloofar; Khosravani, Masoumeh; Mohammadi, Hemn; Sarvestan, Javad (Journal of bodywork and movement therapies, 2024)
OBJECTIVES: This study aimed to investigate the impact of SportsMetrics programs on knee and ankle kinematics, as well as knee-ankle coupling responses during double leg landings among female athletes with dynamic knee valgus (ligament dominance). METHODS: Eighty-four female athletes, including 30 volleyball players, 30 basketball players, and 24 soccer players, were randomly divided into two equal training (TG) and a control groups (CG). The TG underwent 18 sessions of SportsMetrics exercises, while the CG maintained their regular exercise routine. Dynamic knee valgus, lower limb kinematics, and coordination were assessed using the double leg squat and landing error scoring system tests. MAIN OUTCOME MEASURES: The main outcome measures encompassed knee sagittal and frontal kinematics, ankle sagittal kinematics, as well as knee-ankle coordination and its variability. RESULTS: Significant reduction in knee range of motion in the frontal plane was observed across all three sports during landing. The SportsMetrics program tailored for basketball players led to a specific increase in knee flexion. CONCLUSION: The implementation of SportsMetrics effectively modifies ACL injury risk factors, addressing dynamic knee valgus and landing techniques in female athletes. Female athletes displaying dynamic knee valgus are advised to incorporate sport-specific SportsMetrics programs into their training regimens for optimal results.
Keywords: dospělí; Female; Landing coordination; Vector coding; Adult; Volleyball; mladý dospělý; ženské pohlaví; Knee Joint; volejbal; Adolescent; poranění předního zkříženého vazu; Soccer; basketbal; lidé; Kinematics; Knee abduction; fotbal; Range of Motion, Articular; biomechanika; rozsah kloubních pohybů; Basketball; Anterior Cruciate Ligament Injuries; Young Adult; sportovci; Ankle Joint; Athletes; kolenní kloub; mladiství; Biomechanical Phenomena; hlezenní kloub; Humans